Samba and Choro in the Classroom: Enculturation at Colégio Pedro II (São Cristóvão). (4th March 2020) - Harte, Colin
Abstract : This article examines how the performance of samba and choro becomes a process of student enculturation within a Brazilian formal educational context. Musical enculturation is defined as the process of gaining music skills and knowledge through immersion in the music making and music of one's social environment. While the processes of enculturation involve both formal and informal education, this study primarily focuses upon the formal instruction at Colégio Pedro II (São Cristóvão), a federally funded public school in Rio de Janeiro. This research shows that samba and choro were selected by Colégio Pedro II music instructors as culturally important musical forms representative of Rio de Janeiro, historically excluded from formal, public education. The recent inclusion of samba and choro in formal education was made possible by progressive, post-1988, Brazilian educational legislation. I argue that the teaching of samba and choro in the school environment provides students with the necessary participatory skills to engage with the rich musical traditions of samba and choro that are pervasive in Rio de Janeiro as cultivated through the enculturative processes demonstrated at Colégio Pedro II (São Cristóvão) grupo de samba and grupo de choro.